Analisis Sanksi Kebiri Kimia Bagi Pelaku Kejahatan Seksual Terhadap Anak Dalam Perspektif Undang-Undang No. 17 Tahun 2016 Sebagai Perubahan Atas Undang-Undang No. 23 Tahun 2002 Tentang Perlindungan Anak - PRATIWI, RADIYATI; Zaenudin, Fakhri Rizki (Peneliti.net, 2025)
In response to the rise in child sexual abuse, the government has implemented chemical castration as a preventive measure. This punishment lowers testosterone levels and libido in convicted offenders, with the aim of reducing sexual crimes against children. This research has three main objectives: to examine the chemical castration procedure according to Government Regulation No. 70, analyze its implementation, and identify related challenges. The process involves clinical assessment, determination of eligibility, and execution. While intended to curb sexual violence, chemical castration is seen as violating Indonesia's Constitution and international agreements, and it contradicts penal philosophies that prioritize justice and human dignity.